Servqual Analysis on Samsung Libraries, Sungkyunkwan University, Korea: A Study of Tangible - Dewi, Chintia (Department Library of Governance Institut of Home Affairs, 2022)
Background: The rapid growth of information technology and the ease of access to digital collections in recent years have increased the need for physical library services at Samsung Library, Sunkyunkwan University. However, its popularity has not diminished, and it continues to draw crowds from tourists. Purpose: This research aimed to analyze the service quality (servqual) of physical products in the Samsung Library, Sunkyunkwan University. Method: A descriptive qualitative method was adopted using indicators of tangible servqual analysis. Results: The results showed that the dimension of the Library Building Facilities is very good because it combines cultural, academic, and modern civilization architecture with sophisticated technology. The library infrastructure was also adequate, starting from its multipurpose rooms, complete collections, and futuristic, modern, and comfortable reading tables and bookshelves, increasing the comfortability of users. The findings on the display indicators for library staff were very satisfying because they display attractive officers and are equipped with Libo robot facilities. Conclusion: In general, the tangible servqual for the Samsung Library, Sunkyunkwan University, is good, and the physical product is a very important component in attracting users and tourists. Keywords: Tangible Services; Samsung Libraries; Sungkyunkwan University; Servqual Analysis